Hypervolemia and blood alkalinity: Effect on physiological strain in a warm environment - Nelson, M. D.; Stuart-Hill, L. A.; Sleivert, G. G. (International Journal of Sports Physiology and Performance, 2008)
Purpose: To evaluate the influence of acute hypervolemia, achieved through the ingestion of a sodium citrate-rich beverage, on cardiovascular strain and thermoregulatory function, during moderate-intensity aerobic exercise in a warm environment. Sodium citrate`s ability to increase buffering capacity was also assessed. Methods: Twelve endurance-trained athletes completed two blind randomized treatment trials, separated by a minimum of seven days, on a cycle ergometer under heat stress (30.9°C, 64% RH). The subjects ingested 12 mL·kg-1 of (1) Gatorade, the control (CNT), or (2) sodium-citrate plus Gatorade (NaCIT: 170 mmol Na+L-1) before cycling at 15% below ventilatory threshold (VT) for 62 minutes. Core and skin temperature, expired gas samples, heart rate, and perceived exertion were measured throughout exercise. Blood samples were taken before drinking each beverage, before commencing exercise, and throughout the exercise bout. Results: Plasma volume (PV) was significantly expanded in the NaCIT trial (3.6 ± 5.5%) and remained significantly higher throughout exercise in the NaCIT trial compared with the CNT trial (P = .05). No significant differences were found in heart rate, in core and skin temperature, or in the metabolic data between the treatment groups. NaCIT significantly increased [HCO3-], base excess, and pH throughout the trial. Conclusion: Acute oral ingestion of high-sodium citrate beverages before moderate exercise induces mild levels of hypervolemia and improves blood-buffering capacity in humans; however, mild hypervolemia during 62 minutes of moderate exercise does not reduce physiological strain or improve thermoregulation.